The TLR4-MyD88 Signaling Axis Regulates Lung Monocyte Differentiation Pathways in Response to Streptococcus pneumoniae - Sánchez-Tarjuelo, Rodrigo; Cortegano, Isabel; Manosalva, Juliana; Rodríguez, Mercedes; Ruíz, Carolina; Alía, Mario; Prado, María Carmen; Cano, Eva M.; Ferrándiz, María José; de la Campa, Adela G.; Gaspar, María Luisa; de Andrés, Belén (Frontiers in Immunology, 2020)
Streptococcus pneumoniae is the main cause of bacterial pneumonia, which currently produces significant global morbidity and mortality. The initial immune response to this bacterium is induced when the innate system recognizes common motifs expressed by many pathogens, events driven by pattern recognition receptors like the Toll-like family receptors (TLRs). In this study, lung myeloid-cell populations responsible for the innate immune response against S. pneumoniae, and their dependence on TLR4-signalling axis, were analysed in TLR4-/- and Myeloid-Differentiation factor-88 deficient (MyD88-/-) mice. Neutrophils and monocyte-derived cells were recruited in infected mice 3-days post-infection. Compared to wild-type mice, there was an increased bacterial load in both deficient mice strains and an altered innate response, although TLR4-/- mice were more susceptible to bacterial infection. These mice also developed fewer alveolar macrophages, less neutrophil infiltration, impaired Ly6Chigh monocyte differentiation and a disrupted M1-M2 profile. The pro-inflammatory cytokine profile (CXCL1, TNF-α, IL-6 and IL-1β) was also severely affected by the lack of TLR4 and no induction of Th1 was observed in these mice. The respiratory burst (ROS production) after infection was profoundly dampened in TLR4-/- and MyD88-/- mice. These results demonstrate the complex dynamics of myeloid populations, and a key role of the TLR4-signalling axis that involves both the MyD88 and TRIF (Toll/IL-1R domain-containing adaptor-inducing IFN-β) dependent pathways in the innate immune response to S. pneumoniae.